A Case Study on Design and Optimization of Adaptive Civil Structures - Geiger, Florian; Gade, Jan; von Scheven, Malte; Bischoff, Manfred (Frontiers in Built Environment, 2020)
Taking advantage of adaptivity in the field of civil engineering is subject to ongoing research. Integration of adaptive elements in the load bearing structure is already well established in many other engineering fields, albeit mostly for different purposes than withstanding predominantly static loads. First investigations promise substantial material and energy saving potentials also in the field of civil engineering, especially considering high-rise buildings or wide span structures, like roofs or bridges. Adaptive civil structures offer new potentials to tackle current challenges emanating from emission problems and shortage of materials. Therefore, we compare the possible minimum weight designs for different actuator placement approaches and for different structural topologies, fulfilling different constraints for high-rise buildings. We focus on case studies of illustrative examples to show, which advantages and disadvantages can be expected from a specific design. The overarching aim is to learn how truss and beam structures should be designed to exhibit good performance as an adaptive structure.